Enhanced and durable electrocatalytic performance of thin layer PtRu bimetallic alloys on Pd-nanocubes for methanol oxidation reactions. Issue 15 (5th July 2017) - Yousaf, Ammar Bin; Imran, M.; Kasak, Peter; Zavahir, Fathima Sifani; Zaidi, Syed Javaid; Fernandez, Carlos
Abstract : Enhanced and durable electrocatalytic performance of thin layer PtRu bimetallic alloys on Pd-nanocubes for methanol oxidation reactions. Abstract : As a renewable and promising energy devices, direct methanol fuel cells (DMFCs) have attracted a wide range of interest in recent years. The design of electrocatalysts highly influences the performance of DMFCs systems. Herein, PtRu bimetallic alloy nanoparticles have been fabricated onto a Pd nanocube (NC) core material by a facile wet chemical co-precipitation method. Structural and morphological characterization of the catalyst was performed using X-ray photoelectron spectroscopy (XPS) analysis, energy-dispersive X-ray (EDX) spectroscopy, transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), high-angle annular dark-field scanning TEM (HAADF-STEM) elemental mapping and temperature programmed reduction (TPR). The presence of a single TPR peak strongly supported bimetallic Pt–Ru interactions and alloying. The electrocatalytic performance of the as-synthesized PtRu@Pd-NC catalyst for the methanol oxidation reaction (MOR) is studied in HClO4 aqueous solution by cyclic voltammetry (CV), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS), and it is compared with that of a PtRu/C (E-TEK) catalyst. The catalyst has shown the highest specific activity ( ca. 11.44 mA cm −2 at 0.70 V), a lower onset potential and enhanced durability for MOR, which is significantly higher than the commercial PtRu/C (E-TEK) catalyst and other reported Pt/Pd-based catalysts. The results attribute to mutual interactions of the core–shell material that enhance the chemisorption of methanol.